Investigating gender-based code-mixing in core aviation classrooms / Muhammad Shahrul Azhani Shohaimi - Shohaimi, Muhammad Shahrul Azhani (2019)
This research aims to investigate the differences in gender-based code-mixing in an aviation classroom setting. It specifically focuses on examining the patterns of codemixing employed and identifying the reasons for code-mixing based on gender in three different aviation modules' sessions. Three male and three female students who had enrolled in the Aircraft Maintenance Program (AMP) at Allied Aeronautics Training Centre (AATC) were selected based on a preliminary observation. This research employed both quantitative and qualitative approaches in analysing the collected data. The quantitative method was utilised in analysing the frequency of patterns employed by the participants while the qualitative method was employed to analyse participants' reasons for code-mixing. Data on code-mixing were collected through a series of observations and semi-structured interviews. Nine observations on code-mixing practices were audio-recorded with the aid of an observation Schedule. A one-to-one interview session was also conducted with each participant to elicit reasons for codemixing using an interview protocol. The research revealed that there were variations in code-mixing patterns by gender. In terms of patterns, male participants did not show any preferred pattern of code-mixing as compared to female participants who most of the time produced utterances that reflected the insertion pattern. With respect to reasons for code-mixing, both genders showed differences. Male participants code-mixed to ensure the effectiveness of communication and to enable listeners to follow. However, female participants code-mixed due to their fear of fully conversing in English and because of cultural influences, especially concerning the acceptance of English. This research has provided insights into gender-based code-mixing specifically in terms of patterns and reasons which have implications for TVET and ESL teaching and learning. The research, in fact, has helped justify the relevance of code-mixing practices in the classroom for both teachers and students, and, therefore, the Ministry of Higher Education consider the prevalence of this practice. Besides, the Civil Aviation Authority of Malaysia (CAAM) could make the necessary adjustments to the language policy related to the medium of instruction.